Two distinct interstitial macrophage populations coexist across tissues in specific subtissular niches - Chakarov, Svetoslav; Lim, Hwee Ying; Tan, Leonard; Lim, Sheau Yng; See, Peter; Lum, Josephine; Zhang, Xiao-Meng; Foo, Shihui; Nakamizo, Satoshi; Duan, Kaibo; Kong, Wan Ting; Gentek, Rebecca; et al. (Science (American Association for the Advancement of Science), 2019)
Macrophages are a heterogeneous cell population involved in tissue homeostasis, inflammation, and various pathologies. Although the major tissue-resident macrophage populations have been extensively studied, interstitial macrophages (IMs) residing within the tissue parenchyma remain poorly defined. Here we studied IMs from murine lung, fat, heart, and dermis. We identified two independent IM subpopulations that are conserved across tissues: Lyve1 MHCII CX3CR1 (Lyve1 MHCII ) and Lyve1 MHCII CX3CR1 (Lyve1 MHCII ) monocyte-derived IMs, with distinct gene expression profiles, phenotypes, functions, and localizations. Using a new mouse model of inducible macrophage depletion ( ), we found that the absence of Lyve1 MHCII IMs exacerbated experimental lung fibrosis. Thus, we demonstrate that two independent populations of IMs coexist across tissues and exhibit conserved niche-dependent functional programming.